2012
DOI: 10.1128/iai.00506-12
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Lipid A Pyrophosphorylation and Functional lptA Reduces Inflammation by Neisseria Commensals

Abstract: The interaction of the immune system with Neisseria commensals remains poorly understood. We have previously shown that phosphoethanolamine on the lipid A portion of lipooligosaccharide (LOS) plays an important role in Toll-like receptor 4 (TLR4) signaling. For pathogenic Neisseria, phosphoethanolamine is added to lipid A by the phosphoethanolamine transferase specific for lipid A, which is encoded by lptA. Here, we report that Southern hybridizations and bioinformatics analyses of genomic sequences from all e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 64 publications
(95 reference statements)
4
62
0
Order By: Relevance
“…LpxT catalyzes the phosphorylation of Lipid A at the 1-position using undecaprenyl pyrophosphate as a phosphate donor, thus increasing the negative charge of the bacterial surface. This modification is relevant not only for LPS stability, but also significantly affects its endotoxicity, as Lipid A lacking one or both phosphate groups has proven to be less toxic in several bacteria (Kong et al 2011;John et al 2012;Needham and Trent 2013). The effect of temperature on Lipid A decoration has not been extensively explored so far.…”
Section: Discussionmentioning
confidence: 99%
“…LpxT catalyzes the phosphorylation of Lipid A at the 1-position using undecaprenyl pyrophosphate as a phosphate donor, thus increasing the negative charge of the bacterial surface. This modification is relevant not only for LPS stability, but also significantly affects its endotoxicity, as Lipid A lacking one or both phosphate groups has proven to be less toxic in several bacteria (Kong et al 2011;John et al 2012;Needham and Trent 2013). The effect of temperature on Lipid A decoration has not been extensively explored so far.…”
Section: Discussionmentioning
confidence: 99%
“…Phase-variable expression in Neisseria species is more often associated with longer homopolymeric runs of guanine bases, but there is one report of phase variation resulting from a polyadenine tract in the promoter of the porA gene in N. meningitidis (30). Recent studies have also found associations between lipid A phosphorylation, diphosphorylation, and phosphotidyl ethanolamine (PEA) decoration and the potency of TLR4 activation and host inflammatory cytokine production (25,(31)(32)(33). Interestingly, PEA decoration is carried out by an enzyme (LptA) that is encoded in the genomes of both pathogenic Neisseriaceae but not the commensal Neisseriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike N. gonorrhoeae and N. meningitidis, nonpathogenic Neisseria spp. are considered to be noninflammatory, and they very rarely elicit a symptomatic inflammatory response (6).…”
mentioning
confidence: 99%